2017
DOI: 10.3389/fmicb.2017.00164
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Phage Application in the Treatment of Acne Caused by Propionibacterium acnes

Abstract: Propionibacterium acnes is associated with purulent skin infections, and it poses a global problem for both patients and doctors. Acne vulgaris (acne) remains a problem due to its chronic character and difficulty of treatment, as well as its large impact on patients' quality of life. Due to the chronic course of the disease, treatment is long lasting, and often ineffective. Currently there are data regarding isolation of P. acnes phages, and there have been numerous studies on phage killing of P. acnes, but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 96 publications
1
48
0
Order By: Relevance
“…Topical probiotics may also include C. acnes bacteriophages, which are viruses that can lyse host bacteria. Two studies showed that some C. acnes bacteriophages lyse only acne‐associated and uncorrelated (potentially pathogenic) phylotypes, but are often ineffective against phylotypes associated with healthy skin . This potential combination of healthy‐skin‐associated C. acnes together with bacteriophages that target other C. acnes could potentially allow for highly specific strain replacement (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Topical probiotics may also include C. acnes bacteriophages, which are viruses that can lyse host bacteria. Two studies showed that some C. acnes bacteriophages lyse only acne‐associated and uncorrelated (potentially pathogenic) phylotypes, but are often ineffective against phylotypes associated with healthy skin . This potential combination of healthy‐skin‐associated C. acnes together with bacteriophages that target other C. acnes could potentially allow for highly specific strain replacement (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Further support for a role for C. acnes is that acne prevalence decreases with increasing age, likely as a result of decreased sebum production with age, but the change in sebum secretion may be linked to changes in microbiome composition. Although there is promising evidence for the use of lytic formulations with bacteriophages for reducing C. acnes growth in vitro , substantial future work will be required to prove the utility of bacteriophage for treating human acne …”
Section: Acne and Skin Bacteriamentioning
confidence: 99%
“…Although there is promising evidence for the use of lytic formulations with bacteriophages for reducing C. acnes growth in vitro, substantial future work will be required to prove the utility of bacteriophage for treating human acne. 39,40 While much evidence exists supporting the role of C. acnes in acne, the topic remains controversial. C. acnes is also considered a host-beneficial microbe.…”
Section: Acne and Skin Bacteriamentioning
confidence: 99%
“…Then Triethanolamine was added dropwise until the gel consistency and pH is adjusted between 6.8 to 7.4. The final volume was made up to 200g by the addition of distilled water [9][10][11][12][13][14][15][16][17][18][19]. Physical evaluation of gel.…”
Section: Formulation Of Gelmentioning
confidence: 99%
“…Food intake was measured on each day. All animals were divided into four groups [19][20][21]. Histopathology Study.…”
Section: Procedurementioning
confidence: 99%